2007
DOI: 10.1080/09603120701628719
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of tap water lead contamination in Lower Saxony, Germany

Abstract: Lead is known to have numerous adverse effects especially to infants and children. The intake of lead through drinking water is commonly due to metal corrosion in the peripheral water distribution system, especially the user's plumbing. The aim of this project was to assess the present state of drinking water contamination with lead in Lower Saxony and to promote replacement of lead pipes. For this purpose a project was initiated comprising three parts. First, a free examination of drinking water was offered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…It is a neurotoxin and is responsible for the most common type of human metal toxicosis (Berman 1980). Also, studies have linked Pb exposures even at low levels with the increase in blood pressure (Zietz et al 2007) as well as with reduced intelligence quotient in children (Needleman 1992) and with attention disorders (Yule and Rutter 1985). Exposure to lead is cumulative over time.…”
Section: Lead (Pb)mentioning
confidence: 98%
See 1 more Smart Citation
“…It is a neurotoxin and is responsible for the most common type of human metal toxicosis (Berman 1980). Also, studies have linked Pb exposures even at low levels with the increase in blood pressure (Zietz et al 2007) as well as with reduced intelligence quotient in children (Needleman 1992) and with attention disorders (Yule and Rutter 1985). Exposure to lead is cumulative over time.…”
Section: Lead (Pb)mentioning
confidence: 98%
“…The possible long-term effects of chronic exposure to lead present in drinking water are subject to considerable public concern (Zietz et al 2007), and in the analysis of the water samples collected, Pb is in levels above the drinking water guidelines of 0.01 mg/l (WHO 2011b) and the Egyptian standard (EGYPT 2007), but below the irrigation limit. The high concentration of cadmium may come from leaching of metal from soil which contains about 5.5 ppm of Pb in the study area (Salman 2013).…”
Section: Lead (Pb)mentioning
confidence: 99%
“…Significant levels of trace metals could be detected after stagnation of the water in distribution system, especially during night -time (Haider et al, 2002;Vasile et al, 2009Vasile et al, , 2011Zietz et al, 2003Zietz et al, , 2007. All these studies reported increased concentration of lead, cadmium, copper, iron and nickel after stagnation in household tap water in Austria, Germany and Romania.…”
Section: Introductionmentioning
confidence: 93%
“…Exposure to high Pb levels may cause abortion to pregnant women and may damage the organs responsible for sperm production in men. Other studies have linked Pb exposure, even at low concentrations, to an increase of arterial pressure as well as a weak intelligence quotient in children and a disorder in attention [10][11][12]. Also Glover-Kerkvliet [13] reported that exposure high Hg, Au and Pb concentrations is associated with auto-immunity development that drives the immunity system to attack its own cells, mistaking them for invaders.…”
Section: Heavy Metalsmentioning
confidence: 99%